The Implementation Of Flipped Classroom In Promoting Students' Learning Autonomy In A Call Class - Christ Doherti, Eunike Natalia; Wulandari, Mega (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
This research aims at investigatingthe implementation of flipped classroom in CALLclass and how it can improve students’ learning autonomy. This research is a case study. The data gathering techniques used in this study were interviews, observations, and questionnaire and it employed descriptive analysis technique. The result showed that the flipped classroom in CALL class was divided into two main category, namely inside and outside class activities. The study also revealed that flipped classroom promoted students’ learning autonomy in six aspects, namely helping the students determine their learning objectives, define the content and progression, select the methods and techniques to be used, monitor the procedure of their learning strategy, evaluate what they had acquired, and prepare themselves to become teachers.